Reconstruction of the Kinetochore during Meiosis in Fission Yeast Schizosaccharomyces pombe - Hayashi, Aki (The American Society for Cell Biology, 2006)
During the transition from mitosis to meiosis, the kinetochore undergoes significant reorganization, switching from a bipolar to a monopolar orientation. To examine the centromere proteins that are involved in fundamental reorganization in meiosis, we observed the localization of 22 mitotic and 2 meiotic protein components of the kinetochore during meiosis in living cells of the fission yeast. We found that the 22 mitotic proteins can be classified into three groups: the Mis6-like group, the NMS (Ndc80-Mis12-Spc7) group, and the DASH group, based on their meiotic behavior. Mis6-like group proteins remain at the centromere throughout meiosis. NMS group proteins disappear from the centromere at the onset of meiosis and reappear at the centromere in two steps in late prophase. DASH group proteins appear shortly before metaphase of meiosis I. These observations suggest that Mis6-like group proteins constitute the structural basis of the centromere and that the NMS and DASH group proteins reassemble to establish the functional metaphase kinetochore. On the other hand, the meiosis-specific protein Moa1, which plays an important role in forming the meiotic monopolar kinetochore, is loaded onto the centromere significantly earlier than the NMS group, whereas another meiosis-specific protein, Sgo1, is loaded at times similar to the NMS group.